Novice career and technical education teachers participation in professional development in the United States (IR) - Mohd Azlan Mohammad Hussain (2016)
The purpose of this study was to identify the status (focal areas, intensity, and usefulness) of novice Career and Technical Education (CTE) teacher participation in professional development compared to novice teachers from other subject matter areas. Additionally, this study examined relationship between the most in need criteria (qualified to teach from alternative certification, lack of practicum experience and having less teaching experience) and the intensity of novice CTE teachers' participation in professional development. In order to achieve these objectives, this study analyzed the data from the 2011- 2012 National School and Staffing Survey (SASS). A total of7,510 samples in the dataset were selected for the analysis, as they meet with the novice teachers' criteria (had five years or less teaching experience). From that number, 730 of them were novice CTE teachers, while the rest were non-CTE novices. The data has been analyzed using descriptive, binomial logistic, and multinomial logistic analyses. The findings of this study pointed to differences in the focal areas, intensity and usefulness of the professional development in which novice CTE teachers were involved, compared to the non-CTE novices. Compared to the non-CTE novices, novice CTE teachers were more likely to be involved in professional development related to teaching content, instructional computer usage, student discipline and classroom management, and teaching special needs students. Additionally, novice CTE teachers compared to the nOI1- CTE novices have been found more likely to attend longer hours of professional development related to teaching content, instructional computer usage, and student discipline and classroom management. This study also found that novice CTE teachers compared to their counterparts, are more likely to feel that their participations in professional development related to teaching content, instructional computer usage, student discipline and classroom management, and teaching special needs students helped to improve their teaching activities. In regard to novice CTE teachers with the most in need criteria, the study indicates that novice CTE teachers from alternative certification programs, compared to those from traditional teacher training programs were more likely to attend longer hours of professional development related to student discipline and classroom management, and reading instruction.This study provided information on the status of novice CTE teachers' involvement in professional development. This information can be used by novice teachers in planning their future involvement in high quality professional development. In addition, administrators and policy makers may be able to formulate a strategy for encouraging novice teachers to participate in effective professional development programs.